2016
DOI: 10.1002/jmv.24632
|View full text |Cite
|
Sign up to set email alerts
|

Acute viral respiratory infections among children in MERS‐endemic Riyadh, Saudi Arabia, 2012–2013

Abstract: The emergence of the Middle East Respiratory Syndrome (MERS) in Saudi Arabia has intensified focus on Acute Respiratory Infections [ARIs]. This study sought to identify respiratory viruses (RVs) associated with ARIs in children presenting at a tertiary hospital. Children (aged ≤13) presenting with ARI between January 2012 and December 2013 tested for 15 RVs using the Seeplex RV15 kit were retrospectively included. Epidemiological data was retrieved from patient records. Of the 2235 children tested, 61.5% were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 31 publications
4
16
1
Order By: Relevance
“…In 2016, only 9 of 552 cases (1.6%) of MERS-CoV infection were found among pediatric patients. Moreover, the study which was conducted in King Fahad Medical City in Riyadh (KFMC) between January 2012 and December 2013 did not report any MERS-CoV cases among children [26]. e study which was conducted across the Gulf countries for four years by Mahmoud Aly et al between 2012 and 2016 suggests that the prevalence and distribution of MERS-CoV were the highest-risk in elderly aged 60 years or above [14].…”
Section: Discussionmentioning
confidence: 99%
“…In 2016, only 9 of 552 cases (1.6%) of MERS-CoV infection were found among pediatric patients. Moreover, the study which was conducted in King Fahad Medical City in Riyadh (KFMC) between January 2012 and December 2013 did not report any MERS-CoV cases among children [26]. e study which was conducted across the Gulf countries for four years by Mahmoud Aly et al between 2012 and 2016 suggests that the prevalence and distribution of MERS-CoV were the highest-risk in elderly aged 60 years or above [14].…”
Section: Discussionmentioning
confidence: 99%
“…Many other studies have also demonstrated a high incidence of RSV infection and disease among infants less than one year old [36,37]. a recent epidemiological meta-analysis study implicated RSV as one of the most significant pathogens of early childhood and placed it as the second-most-likely single pathogen to cause death in children less than one year of age [38][39][40]. Although there is evidence that maternal antibodies in infants are likely to be important in protection against RSV disease, severe disease was noted in children under six months of age, indicating that maternal RSV-specific antibodies are protective during the first 6-7 months, but this protection may then wane [41].…”
Section: Discussionmentioning
confidence: 99%
“…Prevalence (for 229E, HKU1, NL63, and OC43, unless otherwise specified) Eight countries: 6% in children with ARTIs (ambulatory, >1 yr) 33 Unknown Saudi Arabia: 0% of 2235 children with ARTIs (ambulatory and hospitalized, over 2 yr, 2012-2013) 34 Unknown Brazil: 5% in children with ARTIs (ambulatory and hospitalized, >9 yr) 4 China: 2% in children with fever and upper ARTIs (ambulatory and hospitalized, >5 yr) 35 France: 6% (HCo-OC43) in children and adults with ARTIs (ambulatory and hospitalized, October to April) 5 Hong Wuhan: 2.7 (2.5-3.9) (as of February 2020) 38 2.2 (2.0-2.6)-3.6 (2.9-4.4) (as of January 2020) 50 Zoonotic origin Bats (NL63, 229E) 17,18 Dromedary camels (229E) 19 Cattle (OC43) 20 Civet cats 24,25 (bats as reservoirs) 21,22 Dromedary camels 27 (bats as reservoirs) 21 Pangolin suspected but unproven 51 Outbreak extent and numbers (adults and children) 37 8 d (95% CI: 2.5-23.3 d) 37 8 d (SD 4 d) 45 12 d (SD 3 d) 70 Shedding duration 6 d (3-10 d) in children in daycare 73 Mostly after onset of symptoms 74,75 Mostly after onset of symptoms 70…”
Section: Sars-cov-2mentioning
confidence: 99%
“…34,76,109,110,139,140 In a large case series of 2235 children with acute respiratory tract infection who presented to a tertiary hospital in Saudi Arabia during the MERS-CoV epidemic (2012-2013), none tested positive for MERS-CoV (Table 1). 34 There are 2 small case series of children infected with MERS-CoV: one including 31 children with a mean age of 10 years 60 and the other one only 7 children. 76 In both studies, 42% of children were asymptomatic.…”
Section: Mers-covmentioning
confidence: 99%